Clinical and molecular characterization of three genomic rearrangements at chromosome 22q13.3 associated with autism spectrum disorder. (February 2017) - Chen, Chia-Hsiang; Chen, Hsin-I; Liao, Hsiao-Mei; Chen, Yann-Jang; Fang, Jye-Siung; Lee, Kuei-Fang; Gau, Susan Shur-Fen
Abstract : Objectives: Chromosome 22q13 is a hot region of genomic rearrangements that may result in deletion, duplication, and translocation, and that may lead to neurodevelopmental disorders in affected patients. Materials and methods: We carried out an array-based comparative genomic hybridization analysis to detect copy number variations (CNVs) of genomic DNA in patients with autism spectrum disorders (ASD) who were consecutively recruited into our molecular genetic study of ASD. Karyotyping, fluorescent in-situ hybridization analysis, and real time-quantitative PCR were used for validation tests. Results: We completed a genome-wide CNV analysis of 335 patients with ASD from Taiwan. Three unrelated male patients were found to carry three different CNVs at 22q13.3, respectively, including a de novo terminal deletion of ∼106 kb at 22q13.33, a de novo interstitial duplication of ∼1.8 Mb at 22q13.32–q13.33, and a microdeletion of ∼147 kb at 22q13.33. These three CNVs all involved the dosage change of the SHANK3 gene. The last patient also carried a genomic duplication of ∼3.86 Mb at 19q13.42–q13.4 in addition to a microdeletion of ∼147 kb at 22q13.33. His younger sister also carried these two CNVs, but she had developmental delay and other neurological deficits without ASD. These two CNVs were transmitted from their unaffected father, who carried a balanced translocation between chromosome 22q and 19q. Conclusion: Our data support that recurrent genomic rearrangements at 22q13.3 are part of the genetic landscape of ASD in our patients and changes in SHANK3 dosage are associated with neurodevelopmental disorders. However, the clinical symptoms of patients with 22q13.3 rearrangements can vary depending on other genetic and nongenetic factors, not limited to genes involved in CNVs in this region.